AB0564 THE CONTROVERSIAL ROWELL SYNDROME: TO BE OR NOT TO BE?. (June 2019) - Vaida-Voevod, Daisy AM; Felea, Ioana; Damian, Laura; Pamfil, Cristina; Rednic, Simona
Abstract : Background: Rowell syndrome is a rather rare and highly debated entity, initially defined by Rowell et all as discoid lupus associated with erythema multiforme-like (EM) lesions, positive speckled ANA, RF and Anti-SJT antibody, later known as anti Ro/La antibodies. In 2000, Zeitouni et al extended the definition by including all types of systemic lupus erythematosus (SLE) and proposed major and minor criteria, while in 2012 Torchia et al proposed another set of criteria defining Rowell syndrome as a distinct subtype of chronic cutaneous lupus. To date, Rowell syndrome as a distinct entity remains in question. Objectives: To establish whether patients with clinically suggestive Rowell syndrome, meet the proposed criteria and form a distinct SLE subgroup. Methods: A retrospective study which included SLE patients who associated EM-like lesions was carried out in the Rheumatology Department Cluj-Napoca, between 2008 and 2019. Clinical, immunological and histopathological parameters were recorded. Results: Among 200 patients who fulfilled the 2012 SLICC criteria, 12 patients with target lesions, resembling EM, were identified. Four patients were excluded: 3 were not fully investigated and 1 was My. pneumoniae positive, thus 8 patients were studied. The majority of patients (87.5%) developed the cutaneous lesions after diagnosis. In all cases, the erythematous maculopapular rash with targetoid aspect was present, with poorly defined borders and a dusky center and a diameter between 2 to 6 cm. The lesions extended to the trunk and limbs, sparring the acral and mucosal areas. Five patients associated pruritus. The lesions could not be linked to any viral or bacterial infection in any of the cases. With regard to drug allergies, a link with AZA and HCQ was suspected in three patients – which was infirmed. The majority of patients (87.5%) had negative anti-ds DNA, 87.5% presented speckled pattern ANA, one patient exhibited ANA rods and rings pattern, with a negative serology for B and C hepatitis and no antiviral therapy. Of note, 25% had positive rheumatoid factor, 87.5% had positive anti-Ro antibody and 37.5% of patients exhibited chilblains. The first three classifications were tested on all patients: 25% met Rowell's criteria, 12.5% met Lee's criteria and 87.5% met Zeitouni's criteria, with only 1 patient meeting all 3, and 1 patient meeting none of them. In the cases in which the SLE etiology of the lesion was in question from a clinical point of view, a biopsy was performed. In one case the histopathological examination described lymphocytic infiltrates and few eosinophils in the dermis, suggestive of drug allergy. Interestingly, this patient met all 3 classification criteria. Another report described thin epidermis, parakeratosis, dyskeratosis and spongiosis with dermis and perivascular lymphocytic infiltrate- findings highly suggestive for EM; this report belonged to the patient who met neither of the 3 classifications, but who associated a rods and rings ANA pattern. The third histopathological report was inconclusive. Conclusion: Our study shows that patients with suspected clinical, immunological or histological Rowell syndrome do not meet all studied classifications criteria. Furthermore, studied classifications are incongruent. Should Rowell syndrome be a distinct entity it would most certainly be a very rare one. Further study is needed to better frame LES and EM. References: [1] ROWELL, N. R. (1963). Lupus Erythematosus and Erythema Multiforme-like Lesions. Archives of Dermatology, 88(2), 176. [2] Torchia, D., Romanelli, P., & Kerdel, F. A. (2012). Erythema multiforme and Stevens-Johnson syndrome/toxic epidermal necrolysis associated with lupus erythematosus. Journal of the American Academy of Dermatology, 67(3), 417–421. Disclosure of Interests: None declared